B vitamin supply in plants and humans: the importance of vitamer homeostasis. (27th June 2022) - Liu, Zeguang; Farkas, Peter; Wang, Kai; Kohli, Morgan‐Océane; Fitzpatrick, Teresa B.
SUMMARY: B vitamins are a group of water‐soluble micronutrients that are required in all life forms. With the lack of biosynthetic pathways, humans depend on dietary uptake of these compounds, either directly or indirectly, from plant sources. B vitamins are frequently given little consideration beyond their role as enzyme accessory factors and are assumed not to limit metabolism. However, it should be recognized that each individual B vitamin is a family of compounds (vitamers), the regulation of which has dedicated pathways. Moreover, it is becoming increasingly evident that individual family members have physiological relevance and should not be sidelined. Here, we elaborate on the known forms of vitamins B1, B6 and B9, their distinct functions and importance to metabolism, in both human and plant health, and highlight the relevance of vitamer homeostasis. Research on B vitamin metabolism over the past several years indicates that not only the total level of vitamins but also the oft‐neglected homeostasis of the various vitamers of each B vitamin is essential to human and plant health. We briefly discuss the potential of plant biology studies in supporting human health regarding these B vitamins as essential micronutrients. Based on the findings of the past few years we conclude that research should focus on the significance of vitamer homeostasis – at the organ, tissue and subcellular levels – which could improve the health of not only humans but also plants, benefiting from cross‐disciplinary approaches and novel technologies. Significance Statement: We provide an up‐to‐date review on the metabolism of selected B vitamins in humans and plants in the context of the health of both. We emphasize the significance of vitamer homeostasis, which could improve the health of not only humans but also plants, benefiting from cross‐disciplinary approaches and novel technologies.